공적연금유형에 따른 은퇴자들의 보건의료비지출 결정요인 - 최령; Ryoung Choi; 황병덕; Byung Deog Hwang (Health policy and management, 2015)
Background: This study aims to identify the monthly average medical expenses of public pension recipients, and analyze the determinants of total health and medical expenses and Western and Oriental medicine expenses, medical service expenses, and medical supplies expenses. Methods: This study used the fifth year data of 2013 out of the raw data of the Korean Retirement and Income Study collected by the National Pension Research Institute. This study conducted t-test, analysis of variance, and linear regression to verify publicly the relevance between pension recipients’ general characteristics and health and medical expenses status using IBM SPSS ver. 21.0 for data analysis. Results: It was analyzed that there is a difference in the spending of expenditure and health care costs according to public pension recipients. Medical expenses of the national pensioners was higher compared to the special corporate pensioners. The national pensioner is related expenditure size, education level, family members living together, residential areas, status of spouse, number of chronic illness, and status of limitation in daily life with psychological health status. Conclusion: Therefore, fairness does not occur fire to the medical use between the special corporate pensioners and national pensioners, aggressive of government such as health policy and financial support for the retiree pension policy that reflects the reality intervention would be required.